Organization and management theories in environmental management systems research: A systematic literature review. Issue 1 (17th July 2019) - Todaro, Niccolò Maria; Daddi, Tiberio; Testa, Francesco; Iraldo, Fabio
Abstract: Environmental management systems have attracted considerable attention from organizational and management scholars, owing to their widespread adoption in most industry sectors. Despite the extensive empirical literature, academic research on ISO 14001 and Environmental Management and Audit Scheme (EMAS) remains characterized by a technical and pragmatic connotation and scarce theoretical contribution. As this research field approaches maturity, theoretical elaboration is crucial for assessing the current state of knowledge and identifying pathways for future research. The main objective of the paper is to scrutinize the academic literature on standard‐based environmental management, with a focus on identifying organizational and management theories that contributed to the development of the field in the last decades. By critically analyzing 55 papers, the study points out eight dominant theoretical frameworks, mostly pertaining to the field of strategic management. The paper provides an in‐depth analysis of the objectives and findings of each study in the light of its theory of reference in order to contribute insights on the current state of theoretical elaboration of standard‐based environmental management systems research.